The Shift in The Tradition of Islamic Education in Indonesia from The 19th Century to The Early 21st Century - Saefudin Saefudin (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
This paper examines the Indonesian Islamic education tradition from the 19th Century to the early 21st Century. The data in this paper were obtained from written sources as well as several previous studies. The results reveal that the Islamic education tradition begins with religious recitation, which is taught individually (not collectively or in a classical system) in a teacherâ€™s house, langgar, or surau. The relationship pattern between Islamic (pesantren-madrasah) and the regular education system is associated with Indonesiaâ€™s Islamic education system development. This pattern occurred in the 19th to the beginning of the 21st Century and is divided into two episodes. During the first two centuries (19th and 20th centuries), the Islamic education system (religious sciences organized by individuals, organizations, or government institutions) was still differentiated (convergence or synthesis) from the ordinary school education system (general sciences). At the beginning of the 21st Century, the relationship between the two education systems has indicated knowledge integration, although it is still minimal. So far, it has been rigidly divided between â€œreligious sciencesâ€ on the one hand and â€œgeneral sciencesâ€ on the other, leading to an integrated knowledge discourse. If this pattern is desired, an Islamic boarding school for higher education will be created. In which â€œgeneral knowledgeâ€ is given during the day, and â€œreligious knowledgeâ€ (Al-Qurâ€™an and Kitab) is taught in the evening. This tradition has become a model for curriculum synthesis between the religious sciences and the general sciences to form the Islamic higher education institution.